Longer duration of statin therapy is associated with decreased carotid plaque vascularity by magnetic resonance imaging. (February 2016) - O'Brien, Kevin D.; Hippe, Daniel S.; Chen, Huijun; Neradilek, Moni B.; Probstfield, Jeffrey L.; Peck, Suzanne; Isquith, Daniel A.; Canton, Gador; Yuan, Chun; Polissar, Nayak L.; Zhao, Xue-Qiao; Kerwin, William S.
Abstract: Objective: Plaque neovasculature is a major route for lipoprotein and leukocyte ingress into plaques, and has been identified as a risk factor for carotid plaque disruption. V p, a variable derived from pharmacokinetic modeling of dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI), correlates with plaque neovasculature density. Because lipid-lowering therapy has been associated with regression of neovasculature in animal models, we sought to determine clinical correlates of carotid plaque neovasculature (as assessed by V p ) in participants on statin therapy for established cardiovascular disease. Methods: 98 participants from an AIM-HIGH sub-study underwent DCE-MRI of their carotid arteries. Expert readers who were blinded to all clinical variables analyzed the MR images to measure carotid plaque V p in all participants. Associations between V p and duration of statin therapy and other clinical risk factors were analyzed. Results: Prior duration of statin treatment at enrollment ranged from <1 year (21%) 1–5 years (40%) and >5 years (39%). In univariate analyses, shorter duration of statin therapy (P = 0.01), the presence of metabolic syndrome (P = 0.02), and higher body mass index (P = 0.01) and lipoprotein(a) (P = 0.01) were all significantly associated with higher baseline V p values. In multivariate analyses, significant associations remained between shorter duration of statin therapy (P = 0.004) and lipoprotein(a) (P = 0.04). Conclusions: These are the first human, in vivo findings suggesting a relationship between duration of statin therapy and regression of carotid plaque neovasculature. Future longitudinal studies are warranted both to confirm this finding and to address whether changes in neovasculature may translate into change in risk for plaque disruption. ClinicalTrials.gov Identifiers: NCT00880178, NCT01178320 andNCT00120289 . Highlights: Carotid plaque V p is an imaging-based marker of neovasculature density, previously validated using histology. V p was measured in 98 subjects with established cardiovascular disease. Longer prior duration of statin therapy was associated with lower V p . Higher lipoprotein(a) levels was independently associated with higher V p .